Super wear-resistant anti-skid rubber sole material and preparation method thereof

By adding white carbon black and silicon-containing cashew phenol to the rubber sole material, and using hydrogen bonding, the problem of poor wear resistance of existing rubber sole materials is solved, better wear resistance and anti-slip performance is achieved, and the mechanical properties of the material are improved.

CN119775642AActive Publication Date: 2025-04-08YANGZHOU ZECHUANG SHOE IND CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411939565.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-08
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The wear resistance of existing rubber sole materials is poor, and the anti-slip performance needs to be further improved.

Method used

By adding white carbon black as a reinforcement to natural rubber, and using the prepared silicon-containing cashew phenol-containing polyisoprene rubber structure to form hydrogen bonds with the surface hydroxyl group of white carbon black, the dual effects of plasticization and capacity increase are achieved, and the wear resistance and mechanical properties of sole materials are improved.

Benefits of technology

It significantly improves the wear resistance and anti-slip properties of rubber sole materials, enhances the mechanical properties of the materials, and has a simple process, which is conducive to industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005212290110000031
    Figure BDA0005212290110000031
  • Figure BDA0005212290110000101
    Figure BDA0005212290110000101
  • Figure BDA0005212290110000111
    Figure BDA0005212290110000111
Patent Text Reader

Abstract

The invention relates to the technical field of rubber sole materials, and discloses a super wear-resistant antiskid rubber sole material and a preparation method thereof.The molecular structure of silicon-containing cardanol grafted polyisoprene rubber is similar to the structure of natural rubber, the silicon-containing cardanol grafted polyisoprene rubber and the natural rubber are subjected to a co-crosslinking reaction, sulfur-containing groups in the structure can promote vulcanization, and the wear resistance of the silicon-containing cardanol grafted polyisoprene rubber is improved. The phenolic hydroxyl group in the structure of the rubber can generate hydrogen-bond interaction with the hydroxyl group on the surface of the white carbon black, and the white carbon black is fixed in a matrix like a gripper, so that the dispersity of the white carbon black in the rubber matrix is improved, and the wear resistance of the rubber material is improved; in the structure of the silicon-containing cardanol grafted polyisoprene rubber, the main chain is a silicon-oxygen bond, the bond energy is higher, the silicon-containing cardanol grafted polyisoprene rubber is not easy to break, the chemical property is more stable, the side chain has a flexible long-chain structure, and the side chain and a rubber matrix can form a wound cross-linked net-shaped structure, so that the mechanical property of the rubber sole material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of rubber sole materials, in particular to a super wear-resistant and non-slip rubber sole material and a preparation method thereof. Background Art

[0002] Sole materials are by-products of footwear products. With the development of footwear products, the quality requirements of sole materials are getting higher and higher. Now, most sole materials are made of rubber materials. For shoe rubber, good wear resistance and anti-skid performance is one of the basic functions that sole rubber products should have, and it is also an important indicator to measure the quality of footwear. The wear resistance and anti-skid performance of the sole refers to the anti-skid effect or grip of the sole on the ground. If the anti-skid performance of the sole is not good, it is easy to slip and fall when walking on wet and icy roads. With the prosperous development of the economy and the continuous progress of society, people are making roads and indoor floors smoother and smoother, which makes it more likely to cause frequent falls. Therefore, it is very important to improve the wear resistance and anti-skid performance of the sole material.

[0003] Natural rubber has excellent softness, elasticity and excellent processability, can be applied to various sports, plays a role in shock absorption, and is widely used in sole materials. However, the wear resistance of natural rubber sole materials is insufficient, and the anti-skid performance needs to be improved. In the prior art, fillers such as white carbon black, nano-silicon dioxide, etc. are generally added as reinforcing materials, but inorganic reinforcing materials are prone to large-scale agglomeration in the rubber matrix, resulting in stress concentration and cracks in the rubber, which ultimately affects its wear resistance and anti-skid performance; invention patent CN106832470B discloses an anti-skid rubber sole and a preparation method thereof, which is obtained by vulcanization molding of NBR / PVC emulsion co-precipitated alloy, low melting point polyamide, natural rubber, solution-polymerized styrene-butadiene rubber, brominated butyl rubber, white carbon black and other components in a mold made of space aluminum material. The obtained anti-skid rubber sole has excellent anti-skid performance, but many components are added and the wear resistance of the sole material is not significantly improved.

[0004] Invention patent CN106589499B discloses an anti-oil and anti-slip safety shoe rubber sole and a preparation method thereof. The optimal balance of sole pattern, hardness and anti-oil and anti-slip performance is achieved through pattern design, material selection and material component ratio adjustment. However, it uses high-vinyl solution-polymerized styrene-butadiene rubber that has not been mass-produced. The sample performance is excellent, but the price is expensive, so it is difficult to produce industrially. The present invention aims to add white carbon black as a reinforcing agent to natural rubber, and utilize the phenolic hydroxyl groups in the prepared silicon-containing cardanol grafted polyisoprene rubber structure to form hydrogen bonds with the surface hydroxyl groups of white carbon black to achieve the dual effects of plasticization and volume expansion, while having good compatibility with natural rubber, improving the wear resistance of the sole material, and further improving the mechanical properties of the material. Summary of the invention

[0005] In view of this, the purpose of the present invention is to provide a super wear-resistant and non-slip rubber sole material and a preparation method thereof, so as to solve the problem that the existing rubber soles have poor wear resistance.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A super wear-resistant and non-slip rubber sole material comprises the following components in parts by weight: 100 parts of natural rubber, 20-35 parts of epoxidized natural rubber, 10-20 parts of white carbon black and 2-10 parts of silicon-containing cardanol grafted polyisoprene rubber, 1-3 parts of stearic acid, 2-4 parts of zinc oxide, 1-2 parts of accelerator, 3-5 parts of sulfur and 0.5-1 part of antioxidant.

[0008] The preparation method of silicon-containing cardanol grafted polyisoprene rubber is as follows: under a nitrogen atmosphere, liquid polyisoprene rubber and organosilicon-modified cardanol are added into a reaction flask, reacting at 70-90° C. for 20-40 minutes, adding an initiator azobisisobutyronitrile, continuing the reaction for 1-3 hours, performing Soxhlet extraction, and obtaining silicon-containing cardanol grafted polyisoprene rubber after drying.

[0009] Furthermore, the mass amounts of organosilicon-modified cardanol and azobisisobutyronitrile are 6-10% and 0.2-0.5% of the mass amount of liquid polyisoprene rubber, respectively.

[0010] Further, the preparation method of organosilicon-modified cardanol is:

[0011] Step (1), under a nitrogen atmosphere, add dimethylvinyl chlorosilane and ethanol to a reaction flask, stir evenly, add 4-methoxythiophenol and triethylamine, stir to react, after the reaction is completed, extract with ethyl acetate and deionized water, purify by organic phase column chromatography, and dry to obtain 4-methoxyphenylchlorosilane intermediate.

[0012] Step (2), under a nitrogen atmosphere, add cardanol and 1,4-dioxane to a reaction flask, stir evenly, add 4-methoxyphenylchlorosilane intermediate and sodium hydride, stir to react, after the reaction is completed, recrystallize with acetone, filter and wash to obtain 4-methoxyphenylsilane-modified cardanol.

[0013] Step (3), under nitrogen atmosphere, add 4-methoxyphenylsilane modified cardanol and dichloromethane to a reaction flask, mix well, add boron tribromide, react at 0-20°C for 8-16h, concentrate under reduced pressure, and dry to obtain organosilicon modified cardanol. The preparation reaction formula is as follows:

[0014]

[0015] Furthermore, in step (1), the molar amounts of 4-methoxythiophenol and triethylamine are 102-110% and 150-200% of the molar amount of dimethylvinylchlorosilane, respectively.

[0016] Furthermore, in step (1), the reaction temperature is 35-50° C. and the reaction time is 12-24 h.

[0017] Furthermore, in step (2), the molar amounts of the 4-methoxyphenylchlorosilane intermediate and sodium hydride are 110-130% and 120-150% of the molar amount of cardanol, respectively.

[0018] Furthermore, in step (2), the reaction temperature is 60-80° C. and the reaction time is 5-12 h.

[0019] Furthermore, in step (3), the molar amount of boron tribromide is 150-220% of the molar amount of 4-methoxyphenylsilane-modified cardanol.

[0020] Furthermore, the preparation method is as follows: adding natural rubber to an open mixing mill and mixing over a roller, adding epoxidized natural rubber, white carbon black, silicon-containing cardanol grafted polyisoprene rubber, stearic acid, and zinc oxide for mixing, the mixing temperature is 50-70°C, then adding an accelerator, sulfur and an antioxidant, mixing well and leaving the sheet for 5-12 hours, and then vulcanizing it on a flat vulcanizer to obtain an ultra-wear-resistant and anti-skid rubber sole material.

[0021] Furthermore, the vulcanization temperature is 115-130° C., the vulcanization pressure is 20-30 MPa, and the vulcanization time is 5-10 min.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The invention firstly causes dimethylvinyl chlorosilane and 4-methoxythiophenol to undergo Michael addition reaction under the action of triethylamine to obtain a 4-methoxyphenylchlorosilane intermediate, and then causes a substitution reaction with cardanol to obtain 4-methoxyphenylsilane-modified cardanol, and then removes the methoxy group under the action of boron tribromide to obtain organosilicon-modified cardanol, and then utilizes the double bonds on the long chain of cardanol to graft with liquid polyisoprene rubber to obtain silicon-containing cardanol grafted polyisoprene rubber, and finally mixes and vulcanizes with natural rubber, white carbon black, etc. to obtain a super wear-resistant and non-slip rubber sole material.

[0024] The main structure of natural rubber is "cis-1,4-polyisoprene", and the molecular structure of silicon-containing cardanol grafted polyisoprene rubber also contains a large number of similar structures. Similarities are compatible and co-crosslinking reactions will occur between the two. The sulfur-containing groups in its structure can promote vulcanization, thereby increasing the crosslinking density of the rubber. At the same time, white carbon black has high fluidity and small size effect, forming a denser structure in the material, thereby reducing the friction coefficient of the material surface, so that the material can reduce wear during movement or use. The phenolic hydroxyl groups in its structure can produce hydrogen bonds with the hydroxyl groups on the surface of white carbon black, fixing the white carbon black in the matrix like a gripper, improving the dispersion of white carbon black in the rubber matrix and increasing the wear resistance of the rubber material.

[0025] The main chain in the structure of the silicon-containing cardanol grafted polyisoprene rubber is a silicon-oxygen bond, which has a high bond energy and is not easy to break, is chemically stable, has a small friction coefficient, has good adhesion, and can effectively increase the adhesion and wear resistance of the rubber material; at the same time, its side chain has a flexible long-chain structure, which can form a entangled cross-linked network structure with the rubber matrix, thereby increasing the mechanical properties of the rubber sole material. The sole material prepared by the invention has strong dimensional stability, good compatibility between raw materials, good dispersibility of the filler in the substrate, and a simple preparation process, which is conducive to industrial production. DETAILED DESCRIPTION

[0026] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0027] Cardanol: Provided by Cardolite (Zhuhai, China), light yellow liquid, composed of 41% triene, 36% diene, and 23% monoene, with the structural formula

[0028] Dimethylvinylchlorosilane, CAS number is 1719-58-0.

[0029] 4-Methoxythiophenol, CAS number is 696-63-9.

[0030] Liquid polyisoprene rubber, model YH-LIR-30K, provided by Shenzhen Masini Elastomer Co., Ltd.

[0031] Example 1

[0032] (1) Under nitrogen atmosphere, 45 mmol of dimethylvinyl chlorosilane and 350 mL of ethanol were added to a reaction flask. After stirring, 48.6 mmol of 4-methoxybenzenethiol and 72 mmol of triethylamine were added. The mixture was reacted at 45° C. for 16 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was purified by column chromatography and dried to obtain a 4-methoxyphenylchlorosilane intermediate.

[0033] (2) Under nitrogen atmosphere, 40 mmol of cardanol and 660 mL of 1,4-dioxane were added to a reaction flask. After stirring, 50 mmol of 4-methoxyphenylsilyl chloride intermediate and 54 mmol of sodium hydride were added. The mixture was reacted at 70 °C for 10 h, and recrystallized from acetone. After filtering and washing, 4-methoxyphenylsilane-modified cardanol was obtained.

[0034] (3) Under nitrogen atmosphere, 35 mmol of 4-methoxyphenylsilane-modified cardanol and 1120 mL of dichloromethane were added to a reaction flask. After mixing, 70 mmol of boron tribromide was added. The mixture was reacted at 10° C. for 12 h, and then concentrated under reduced pressure and dried to obtain organosilicon-modified cardanol.

[0035] (4) Under nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 6 g of organosilicon-modified cardanol were added to a reaction flask, and the mixture was reacted at 80° C. for 30 min. 0.3 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 2 h. The mixture was subjected to Soxhlet extraction and dried to obtain silicon-containing cardanol-grafted polyisoprene rubber.

[0036] (5) 100 g of natural rubber was added to an open mill and mixed over a roller. 25 g of epoxidized natural rubber, 15 g of white carbon black, 2 g of silicon-containing cardanol grafted polyisoprene rubber, 2 g of stearic acid, and 3 g of zinc oxide were added for mixing at a mixing temperature of 60 ° C. Then, 1.5 g of accelerator DM, 3.5 g of sulfur, and 0.8 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 8 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 120 ° C, a vulcanization pressure of 25 MPa, and a vulcanization time of 8 min to obtain an ultra-wear-resistant and anti-skid rubber sole material.

[0037] Example 2

[0038] (1) Under nitrogen atmosphere, 80 mmol of dimethylvinyl chlorosilane and 400 mL of ethanol were added to a reaction flask. After stirring, 81.6 mmol of 4-methoxythiophenol and 120 mmol of triethylamine were added. The mixture was reacted at 50° C. for 12 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was purified by column chromatography and dried to obtain a 4-methoxyphenylchlorosilane intermediate.

[0039] (2) Under nitrogen atmosphere, 75 mmol of cardanol and 750 mL of 1,4-dioxane were added to a reaction flask. After stirring, 82.5 mmol of 4-methoxyphenylsilyl chloride intermediate and 90 mmol of sodium hydride were added. The mixture was reacted at 80 °C for 5 h, and recrystallized from acetone. After filtering and washing, 4-methoxyphenylsilane-modified cardanol was obtained.

[0040] (3) Under a nitrogen atmosphere, 70 mmol of 4-methoxyphenylsilane-modified cardanol and 1750 mL of dichloromethane were added to a reaction flask. After mixing evenly, 105 mmol of boron tribromide was added. The mixture was reacted at 20° C. for 8 h, concentrated under reduced pressure, and dried to obtain organosilicon-modified cardanol.

[0041] (4) Under nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 7 g of organosilicon-modified cardanol were added to a reaction flask, and the mixture was reacted at 90° C. for 20 min. 0.2 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 1 h. The mixture was subjected to Soxhlet extraction and dried to obtain silicon-containing cardanol-grafted polyisoprene rubber.

[0042] (5) 100 g of natural rubber was added to an open mill and mixed over a roller. 20 g of epoxidized natural rubber, 10 g of white carbon black, 4 g of silicon-containing cardanol grafted polyisoprene rubber, 3 g of stearic acid, and 2 g of zinc oxide were added for mixing at a mixing temperature of 70 ° C. Then, 1 g of accelerator DM, 3 g of sulfur, and 0.5 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 5 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 130 ° C, a vulcanization pressure of 30 MPa, and a vulcanization time of 5 min to obtain an ultra-wear-resistant and anti-skid rubber sole material.

[0043] Example 3

[0044] (1) Under nitrogen atmosphere, 35 mmol of dimethylvinyl chlorosilane and 350 mL of ethanol were added to a reaction flask. After stirring, 38.5 mmol of 4-methoxythiophenol and 70 mmol of triethylamine were added. The mixture was reacted at 35° C. for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was purified by column chromatography and dried to obtain a 4-methoxyphenylchlorosilane intermediate.

[0045] (2) Under nitrogen atmosphere, 30 mmol of cardanol and 450 mL of 1,4-dioxane were added to a reaction flask. After stirring, 39 mmol of 4-methoxyphenylsilyl chloride intermediate and 45 mmol of sodium hydride were added. The mixture was reacted at 60 °C for 12 h, and recrystallized from acetone. After filtering and washing, 4-methoxyphenylsilane-modified cardanol was obtained.

[0046] (3) Under a nitrogen atmosphere, 25 mmol of 4-methoxyphenylsilane-modified cardanol and 1000 mL of dichloromethane were added to a reaction flask. After mixing evenly, 62.5 mmol of boron tribromide was added, and the mixture was reacted at 0° C. for 16 h. The mixture was concentrated under reduced pressure and dried to obtain organosilicon-modified cardanol.

[0047] (4) Under nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 8 g of organosilicon-modified cardanol were added to a reaction flask, and the mixture was reacted at 70° C. for 40 min. 0.5 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 3 h. The polyisoprene rubber grafted with silicon-containing cardanol was obtained after Soxhlet extraction and drying.

[0048] (5) 100 g of natural rubber was added to an open mill and mixed over a roller. 35 g of epoxidized natural rubber, 20 g of white carbon black, 6 g of silicon-containing cardanol grafted polyisoprene rubber, 3 g of stearic acid, and 4 g of zinc oxide were added for mixing at a mixing temperature of 70 ° C. Then, 2 g of accelerator DM, 5 g of sulfur, and 1 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 12 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 115 ° C, a vulcanization pressure of 20 MPa, and a vulcanization time of 10 min to obtain an ultra-wear-resistant and anti-skid rubber sole material.

[0049] Example 4

[0050] (1) Under nitrogen atmosphere, 50 mmol of dimethylvinyl chlorosilane and 300 mL of ethanol were added to a reaction flask. After stirring, 52.5 mmol of 4-methoxythiophenol and 82.5 mmol of triethylamine were added. The mixture was reacted at 40° C. for 16 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was purified by column chromatography and dried to obtain a 4-methoxyphenylchlorosilane intermediate.

[0051] (2) Under nitrogen atmosphere, 40 mmol of cardanol and 52 mL of 1,4-dioxane were added to a reaction flask. After stirring, 50 mmol of 4-methoxyphenylsilyl chloride intermediate and 52.8 mmol of sodium hydride were added. The mixture was reacted at 75 °C for 9 h. The mixture was recrystallized from acetone and filtered and washed to obtain 4-methoxyphenylsilane-modified cardanol.

[0052] (3) Under a nitrogen atmosphere, 30 mmol of 4-methoxyphenylsilane-modified cardanol and 1000 mL of dichloromethane were added to a reaction flask. After mixing evenly, 55.5 mmol of boron tribromide was added. The mixture was reacted at 5° C. for 15 h, concentrated under reduced pressure, and dried to obtain organosilicon-modified cardanol.

[0053] (4) Under nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 9 g of organosilicon-modified cardanol were added to a reaction flask, and the mixture was reacted at 85° C. for 35 min. 0.3 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 2 h. The polyisoprene rubber grafted with silicon-containing cardanol was obtained after Soxhlet extraction and drying.

[0054] (5) 100 g of natural rubber was added to an open mill and mixed over a roller. 30 g of epoxidized natural rubber, 12 g of white carbon black, 8 g of silicon-containing cardanol grafted polyisoprene rubber, 2 g of stearic acid, and 3 g of zinc oxide were added for mixing at a mixing temperature of 65 ° C. Then, 2 g of accelerator DM, 4 g of sulfur, and 0.8 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 10 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 120 ° C, a vulcanization pressure of 24 MPa, and a vulcanization time of 6 min to obtain an ultra-wear-resistant and anti-skid rubber sole material.

[0055] Example 5

[0056] (1) Under nitrogen atmosphere, 25 mmol of dimethylvinyl chlorosilane and 150 mL of ethanol were added to a reaction flask. After stirring, 26.5 mmol of 4-methoxybenzenethiol and 40 mmol of triethylamine were added. The mixture was reacted at 45° C. for 24 h. The mixture was extracted with ethyl acetate and deionized water. The organic phase was purified by column chromatography and dried to obtain a 4-methoxyphenylchlorosilane intermediate.

[0057] (2) Under nitrogen atmosphere, 20 mmol of cardanol and 260 mL of 1,4-dioxane were added to a reaction flask. After stirring, 23 mmol of 4-methoxyphenylsilyl chloride intermediate and 27 mmol of sodium hydride were added. The mixture was reacted at 70 °C for 12 h, and recrystallized from acetone. After filtering and washing, 4-methoxyphenylsilane-modified cardanol was obtained.

[0058] (3) Under nitrogen atmosphere, 15 mmol of 4-methoxyphenylsilane-modified cardanol and 525 mL of dichloromethane were added to a reaction flask. After mixing evenly, 27 mmol of boron tribromide was added. The mixture was reacted at 0° C. for 16 h, concentrated under reduced pressure, and dried to obtain organosilicon-modified cardanol.

[0059] (4) Under nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 10 g of organosilicon-modified cardanol were added to a reaction flask, and the mixture was reacted at 90° C. for 30 min. 0.4 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 3 h. The mixture was subjected to Soxhlet extraction and dried to obtain silicon-containing cardanol-grafted polyisoprene rubber.

[0060] (5) 100 g of natural rubber was added to an open mill and mixed over a roller. 30 g of epoxidized natural rubber, 12 g of white carbon black, 10 g of silicon-containing cardanol grafted polyisoprene rubber, 2 g of stearic acid, and 3 g of zinc oxide were added for mixing at a mixing temperature of 60 ° C. Then, 2 g of accelerator DM, 5 g of sulfur, and 0.5 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 10 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 125 ° C, a vulcanization pressure of 22 MPa, and a vulcanization time of 10 min to obtain an ultra-wear-resistant and anti-skid rubber sole material.

[0061] Comparative Example 1

[0062] (1) Under nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 6 g of 4-methoxyphenylsilane-modified cardanol (prepared in Example 1) were added to a reaction flask, and the mixture was reacted at 80° C. for 30 min. 0.3 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 2 h. The mixture was subjected to Soxhlet extraction and dried to obtain 4-methoxyphenylsilane cardanol-grafted polyisoprene rubber.

[0063] (2) 100 g of natural rubber was added to an open mill and mixed over a roller. 25 g of epoxidized natural rubber, 15 g of white carbon black, 2 g of 4-methoxyphenylsilane cardanol grafted polyisoprene rubber, 2 g of stearic acid, and 3 g of zinc oxide were added for mixing at a mixing temperature of 60°C. Then, 1.5 g of accelerator DM, 3.5 g of sulfur, and 0.8 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 8 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 120°C, a vulcanization pressure of 25 MPa, and a vulcanization time of 8 min to obtain a rubber sole material.

[0064] Comparative Example 2

[0065] (1) Under a nitrogen atmosphere, 100 g of liquid polyisoprene rubber and 6 g of cardanol were added to a reaction flask, and the mixture was reacted at 80° C. for 30 min. 0.3 g of initiator azobisisobutyronitrile was added, and the reaction was continued for 2 h. The mixture was subjected to Soxhlet extraction and dried to obtain cardanol-grafted polyisoprene rubber.

[0066] (2) 100 g of natural rubber was added to an open mill and mixed over a roller. 25 g of epoxidized natural rubber, 15 g of white carbon black, 2 g of cardanol grafted polyisoprene rubber, 2 g of stearic acid, and 3 g of zinc oxide were added for mixing at a mixing temperature of 60°C. Subsequently, 1.5 g of accelerator DM, 3.5 g of sulfur, and 0.8 g of antioxidant RD were added. The mixture was mixed and allowed to stand for 8 h. The mixture was then vulcanized on a flat vulcanizer at a vulcanization temperature of 120°C, a vulcanization pressure of 25 MPa, and a vulcanization time of 8 min to obtain a rubber sole material.

[0067] Comparative Example 3

[0068] Add 100g of natural rubber into an open mixing mill and mix over a roller. Add 25g of epoxidized natural rubber, 15g of white carbon black, 2g of stearic acid and 3g of zinc oxide for mixing at a mixing temperature of 60°C. Then add 1.5g of accelerator DM, 3.5g of sulfur and 0.8g of antioxidant RD. Mix well and let the mixture rest for 8h. Then vulcanize it on a flat vulcanizer at a vulcanization temperature of 120°C, a vulcanization pressure of 25MPa and a vulcanization time of 8min to obtain a rubber sole material.

[0069] DIN abrasion performance test: The test was conducted in accordance with GB 9867-2008 and a DIN abrasion testing machine. The prepared rubber sole material was made into a cylindrical shape with a diameter of 16 mm and a height of 8 mm. The test wear stroke was 40 mm (equivalent to 84 r), and the average value was taken after 5 measurements.

[0070] Table 1 Wear resistance test

[0071]

[0072]

[0073] From the test results in the above table, it can be seen that with the increase of the content of silicon-containing cardanol grafted polyisoprene rubber, the DIN wear volume of the rubber sole material gradually decreases, and the wear volume in Example 5 is only 85.5 mm 3 This is because, on the one hand, the double bonds in the long chain of cardanol can be bonded with the double bonds of polyisoprene rubber, improving the compatibility with the matrix rubber. The sulfur-containing groups in its structure can promote vulcanization, thereby increasing the crosslinking density of the rubber. At the same time, silica has high fluidity and small size effect, forming a denser structure in the material, thereby reducing the friction coefficient on the surface of the material, so that the material can reduce wear during movement or use. The phenolic hydroxyl groups in its structure can produce hydrogen bonds with the hydroxyl groups on the surface of silica, fixing silica in the matrix like a gripper, improving the dispersion of silica in the rubber matrix, and increasing the wear resistance of the rubber material. On the other hand, the main chain in the structure of silicon-containing cardanol grafted polyisoprene rubber is a silicon-oxygen bond, which has a high bond energy and is not easy to break, has relatively stable chemical properties, a small friction coefficient, and good adhesion, which can effectively increase the adhesion and wear resistance of the rubber material.

[0074] Comparative Example 1 does not contain phenolic hydroxyl groups and cannot produce hydrogen bonds with white carbon black, resulting in poor dispersibility and affected wear resistance; Comparative Example 2 does not contain an organosiloxane structure and has a larger DIN wear volume; Comparative Example 3 does not contain long chains of organosilicon and cardanol and has the worst wear resistance.

[0075] Anti-slip performance test: Refer to STM603 of British SATRA company and TM144 standard, use anti-slip tester to test dry and wet anti-slip coefficients in smooth state.

[0076] Table 2 Anti-slip performance test

[0077]

[0078]

[0079] The anti-slip coefficient, also known as the friction coefficient, is an indicator used to measure the friction of an object's surface. In certain situations, such as the friction between the sole and the ground, the size of the anti-slip coefficient directly affects the grip and anti-slip performance of the shoe; generally speaking, the larger the anti-slip coefficient, the greater the friction between objects, that is, the better the grip of the object on the surface, which can provide better stability and safety; from the test results in the above table, it can be seen that with the increase of the content of silicon-containing cardanol grafted polyisoprene rubber, the anti-slip coefficient of the rubber sole material gradually increases. This is because the main structure of natural rubber is "cis-1,4-polyisoprene", and the molecular structure of silicon-containing cardanol grafted polyisoprene rubber also contains a large number of similar structures, which are similar and compatible and will undergo a co-crosslinking reaction between the two, and produce hydrogen bonds with white carbon black, which increases the anti-slip coefficient and enhances the anti-slip ability.

[0080] Mechanical properties test: An electronic tensile testing machine was used to test the tensile properties and tearing properties in accordance with GB / T 528-2009 and GB / T529-2008 respectively.

[0081] Table 3 Mechanical properties test

[0082]

[0083]

[0084] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes. They can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the embodiments shown and described herein.

Claims

1. A super wear-resistant and non-slip rubber sole material, characterized in that: The rubber sole material comprises the following components in parts by weight: 100 parts of natural rubber, 20-35 parts of epoxidized natural rubber, 10-20 parts of white carbon black and 2-10 parts of silicon-containing cardanol grafted polyisoprene rubber, 1-3 parts of stearic acid, 2-4 parts of zinc oxide, 1-2 parts of accelerator, 3-5 parts of sulfur and 0.5-1 part of antioxidant; The preparation method of the silicon-containing cardanol grafted polyisoprene rubber is as follows: under a nitrogen atmosphere, liquid polyisoprene rubber and organosilicon-modified cardanol are added into a reaction flask, reacting at 70-90° C. for 20-40 minutes, adding an initiator azobisisobutyronitrile, continuing the reaction for 1-3 hours, performing Soxhlet extraction, and obtaining the silicon-containing cardanol grafted polyisoprene rubber after drying.

2. The super wear-resistant and non-slip rubber sole material according to claim 1, characterized in that: The mass amounts of the organosilicon-modified cardanol and azobisisobutyronitrile are 6-10% and 0.2-0.5% of the mass amount of the liquid polyisoprene rubber respectively.

3. The super wear-resistant and non-slip rubber sole material according to claim 1, characterized in that: The preparation method of the organosilicon-modified cardanol is: Step (1), under a nitrogen atmosphere, add dimethylvinyl chlorosilane and ethanol to a reaction flask, stir evenly, add 4-methoxythiophenol and triethylamine, stir to react, after the reaction is completed, extract with ethyl acetate and deionized water, purify by organic phase column chromatography, and dry to obtain a 4-methoxyphenylchlorosilane intermediate; Step (2), under a nitrogen atmosphere, add cardanol and 1,4-dioxane to a reaction flask, stir evenly, add 4-methoxyphenylchlorosilane intermediate and sodium hydride, stir to react, after the reaction is completed, recrystallize with acetone, filter and wash to obtain 4-methoxyphenylsilane-modified cardanol; Step (3), under a nitrogen atmosphere, add 4-methoxyphenylsilane-modified cardanol and dichloromethane to a reaction flask, mix well, add boron tribromide, react at 0-20° C. for 8-16 h, concentrate under reduced pressure, and obtain organosilicon-modified cardanol after drying.

4. The super wear-resistant and non-slip rubber sole material according to claim 3, characterized in that: In the step (1), the molar amounts of 4-methoxythiophenol and triethylamine are 102-110% and 150-200% of the molar amount of dimethylvinylchlorosilane, respectively.

5. The super wear-resistant and non-slip rubber sole material according to claim 3, characterized in that: In the step (1), the reaction temperature is 35-50° C. and the reaction time is 12-24 h.

6. The super wear-resistant and non-slip rubber sole material according to claim 3, characterized in that: In the step (2), the molar amounts of the 4-methoxyphenylchlorosilane intermediate and sodium hydride are 110-130% and 120-150% of the molar amount of cardanol, respectively.

7. The super wear-resistant and non-slip rubber sole material according to claim 3, characterized in that: In the step (2), the reaction temperature is 60-80° C. and the reaction time is 5-12 h.

8. The super wear-resistant and non-slip rubber sole material according to claim 3, characterized in that: The molar amount of boron tribromide in step (3) is 150-220% of the molar amount of 4-methoxyphenylsilane-modified cardanol.

9. A method for preparing the super wear-resistant and non-slip rubber sole material according to any one of claims 1 to 8, characterized in that: The preparation method comprises the following steps: adding natural rubber to an open mill and mixing it over a roller, adding epoxidized natural rubber, white carbon black, silicon-containing cardanol grafted polyisoprene rubber, stearic acid and zinc oxide for mixing, wherein the mixing temperature is 50-70° C., then adding an accelerator, sulfur and an antioxidant, mixing well, leaving the mixture to rest for 5-12 hours, and then vulcanizing the mixture in a flat vulcanizer to obtain a super wear-resistant and non-slip rubber sole material.

10. The method for preparing the super wear-resistant and non-slip rubber sole material according to claim 9, characterized in that: The vulcanization temperature is 115-130° C., the vulcanization pressure is 20-30 MPa, and the vulcanization time is 5-10 min.

Citation Information

Patent Citations

  • A rubber sole for oil-resistant safety shoes and its preparation method

    CN106589499B

  • A kind of antiskid rubber sole and preparation method thereof

    CN106832470B

  • Super abrasion-resistant rubber for soles and preparation method for super abrasion-resistant rubber

    CN102898694A

  • Anti-skid tire rubber prepared from epoxidized natural rubber and preparation method thereof

    CN106084327A

  • Wear-resistant sole and production process thereof

    CN114276590A